Effect of Mass Variation of Pepper Leaves on Essential Oil Extraction Via Microwave Assisted Extraction (MAE): Pengaruh Variasi Massa Daun Lada Pada Proses Ekstraksi Minyak Atsiri Via Microwave-Assisted Extraction (MAE) - Hamzah Fansuri; Adhiksana, Arief (Fakultas Teknik, Universitas Brawijaya, 2024)
Microwave-Assisted Extraction (MAE) is one of the modern technologies that offer advantages in terms of time and efficiency compared to conventional methods. However, few studies still examine the effect of mass variation on the yield of essential oil produced through the MAE method. This study aims to evaluate the effect of variation in the mass of pepper leaves on the yield of essential oil obtained by the MAE method. This study also aims to determine the optimum mass that gives the highest yield. The extraction was carried out at a microwave power of 600 Watts, a temperature of 105 ºC for 2 hours, using water as a solvent for various pepper leaf masses. The effect of material mass variation on essential oil yield was analyzed and compared. The results showed that the essential oils obtained had a specific gravity of 0.8717, a refractive index of 1.485 Brix, and an acid number of 0.9211 mg/g, respectively. Furthermore, the results also obtained the optimum mass of pepper leaf material at 300 grams with a yield of 0.27%. We believe this study can be a reference for selecting the best mass of material from pepper leaves for essential oil production for further research.